The Implementation of Trump’s Energy Dominance Policy in Central European Countries - Karolina Gawron-Tabor; Tadahiro Yamada (European Journal of American Studies)
An important element of the energy policy of the administration of 45th President of the United States, Donald Trump, was to increase the sale of American LNG abroad and gain global dominance in the energy field. This policy was also directed toward Europe. The article aims to analyze how energy cooperation between the United States and Central European countries (Hungary, Slovakia, the Czech Republic, and Poland) developed during Donald Trump’s presidency (2017-2021). The research addresses the extent to which Central European countries were the place where the Trump administration’s energy policy was implemented; Did Central European countries treat the US administration’s policy in similar ways? What might have resulted from the different approaches of individual countries? The method adopted in the article is a case study and process tracing. Content and discourse analysis are also employed. To achieve the goal of the paper, the Trump administration’s energy dominance policy will be analyzed first. Next, the US energy relations with Hungary, Slovakia, the Czech Republic, and Poland will be examined. Of the Central European countries, only Poland implemented the premises of the Trump administration’s policy. The differences between the countries analyzed originated in different attitudes towards Russia and the desire to make their energy sectors independent of Moscow.